EFFECT OF AVERAGING INSTANTANEOUS ACOUSTIC ENERGY NOISE FOR DISTRIBUTION STATISTICS BOROUGH - , В. О., В. Е., A. І. (Municipal economy of cities. Series: «Economy science», 2016)
Environmental protection, sustainable use of natural resources, environmental safety of human life is an essential condition for sustainable economic and social development of any country. The introduction of modern industry of new technological processes, including power generation and electronics, increased capacity of the process equipment, the use of advanced means of land, air and water transport, numerous domestic and engineering equipment, mechanization of production processes, the widespread development of television, radio, radar, use of high-frequency electromagnetic energy in various spheres of the national economy, as well as in everyday life, have led to the fact that the person in the conditions of production, and the house is constantly exposed to the influence of intense noise, vibration, electromagnetic radiation and in some cases - ionizing radiation. According to the non-permanent urban area of Kharkov noise sample surveys defined view of the empirical distribution function of the instantaneous acoustic energy levels and the impact of the choice of the value of the reference interval of averaging measurement data distribution statistics that approximate indicators of noise pollution urban area. The method of statistical tests proved that the increase in the value of the reference interval to approximate the distribution statistics to the normal, reduction of variance statistics and improve the accuracy of estimates of the noise pollution indicators of the urban area. Keywords: noise pollution, noise pollution indicators, full-scale measurements.